Shifting from Static to Hybrid Architecture Through Flexible Spatial Systems - Michael Hendryanto; Kristanti Dewi Paramita; Yandi Andri Yatmo (Universitas Sebelas Maret Surakarta, 2025)
The rapid pace of urban change and architecture in a constant state of flux have made traditional and static design strategies struggle to adapt to dynamic environments. Prescribed and predictive programs often become obsolete as they no longer correspond to their intended function and representation, making architectural hybridity increasingly important. Hybridity here focuses on multifunctional spaces, approaching the disjunction of events across 15 public building types to identify the interchangeable relation of their essential elements. Similarities of their essence then are formed as conjunctions into a spatial organization catalogue through flexible strategies such as open-plan configurations, double-helix ramp systems, modular furniture systems, and platform mechanisms capable of accommodating diverse activities within a single structure. This design approach aims to maximize space utilization so it can be easily reconfigured to suit different activities and foster more vibrant and dynamic spaces. By manipulating conflict and combining shared essentials through flexibility and modular systems, this approach offers new spaces and realities.